Pengaruh Kemampuan Kerja Terhadap Produktivitas Karyawan Pemanenan Pada PT. YZ Kabupaten Bengkalis - Putra, Eka (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
To achieve this goal, a study was conducted using a sample of 50 people, using a random census method. Methods of data analysis using simple linear regression. Based on the results of work ability testing has a significant effect on employee productivity Harvesting at PT. YZ, Bengkalis Regency, this is proven based on the t test, it found that t-count is greater than t-table (5.797 > 2.011). The value of R. Square (R2) = (0.642 X 0.642 = 0.412) or 41.2%, the percentage of contribution or contribution of the workability variable to the productivity variable is 0.412 or 41.2% while the remaining 68.8% is influenced by other variables that ignored or not examined in this study. Recommendations that can be submitted It is expected that work supervision of employees must be further improved because from the respondents' answers about the field foreman continuing to supervise harvester activities the lowest response was in the statement quite agree, it can be said that supervision must be a top priority for employees.